Chromosome-free bacterial cells are safe and programmable platforms for synthetic biology - Fan, C; Fan, C; Davidson, PA; Davidson, PA; Habgood, R; Zeng, H; Zeng, H; Lueangwattanapong, K; Lueangwattanapong, K; Huang, W (National Academy of Sciences, 2020)
A new type of chromosome-free cells called SimCells (simple cells) has been generated from Escherichia coli, Pseudomonas putida and Ralstonia eutropha. The removal of the native chromosomes of these bacteria was achieved by double-stranded breaks made by heterologous I-CeuI endonuclease, and the degradation activity of endogenous nucleases. We have shown that the cellular machinery remained functional in these chromosome-free SimCells and were able to process various genetic circuits. This includes the glycolysis pathway (composed of 10 genes) and inducible genetic circuits. It was found that the glycolysis pathway significantly extended longevity of SimCells due to its ability to regenerate ATP and NADH/NADPH. The SimCells were able to continuously express synthetic genetic circuits for 10 days after chromosome removal. As a proof of principle, we demonstrated that SimCells can be used as a safe agent (as they cannot replicate) for bacterial therapy. SimCells were used to synthesize catechol (a potent anti-cancer drug) from salicylic acid to inhibit lung, brain, and soft-tissue cancer cells. SimCells represent a novel and simplified synthetic biology chassis that can be programmed to manufacture and deliver products safely without interference from the host genome.